Elevated levels of procoagulant plasma microvesicles in dialysis patients. - James O Burton (Public Library of Science (PLoS), 2013)
Cardiovascular (CV) death remains the largest cause of mortality in dialysis patients, unexplained by traditional risk factors. Endothelial microvesicles (EMVs) are elevated in patients with traditional CV risk factors and acute coronary syndromes while platelet MVs (PMVs) are associated with atherosclerotic disease states. This study compared relative concentrations of circulating MVs from endothelial cells and platelets in two groups of dialysis patients and matched controls and investigated their relative thromboembolic risk. MVs were isolated from the blood of 20 haemodialysis (HD), 17 peritoneal dialysis (PD) patients and 20 matched controls. Relative concentrations of EMVs (CD144(+ ve)) and PMVs (CD42b(+ ve)) were measured by Western blotting and total MV concentrations were measured using nanoparticle-tracking analysis. The ability to support thrombin generation was measured by reconstituting the MVs in normal plasma, using the Continuous Automated Thrombogram assay triggered with 1µM tissue factor. The total concentration of MVs as well as the measured sub-types was higher in both patient groups compared to controls (p<0.05). MVs from HD and PD patients were able to generate more thrombin than the controls, with higher peak thrombin, and endogenous thrombin potential levels (p<0.02). However there were no differences in either the relative quantity or activity of MVs between the two patient groups (p>0.3). Dialysis patients have higher levels of circulating procoagulant MVs than healthy controls. This may represent a novel and potentially modifiable mediator or predictor of occlusive cardiovascular events in these patients.